2010
DOI: 10.1007/s12630-010-9386-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical update: Which local anesthetic drug for pediatric caudal block provides optimal efficacy with the fewest side effects?

Abstract: Purpose The purpose of this evidence-based clinical update is to identify the best evidence when selecting a long-acting local anesthetic agent for single-shot pediatric caudal anesthesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 30 publications
0
36
0
2
Order By: Relevance
“…Depending on the concentration of the local anesthetic and evaluation time, motor block may be observed after caudal block. 13,20,21 None of our patients presented motor block when examined before transfer from PACU to the ward, otherwise reported in the literature. None of the patients had defecation problems caused by the anal sphincter motor insufficiency after the pudendal nerve block.…”
Section: Discussionmentioning
confidence: 58%
“…Depending on the concentration of the local anesthetic and evaluation time, motor block may be observed after caudal block. 13,20,21 None of our patients presented motor block when examined before transfer from PACU to the ward, otherwise reported in the literature. None of the patients had defecation problems caused by the anal sphincter motor insufficiency after the pudendal nerve block.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, another weakness worth mentioning is the significant heterogeneity we encountered. The local anesthetics all varied, although ropivacaine, bupivacaine, and levobupivacaine were found to be equivalent in terms of efficacy37; the concentrations of the local anesthetic were different, which could have influenced the analgesic effects and side effects. Additionally, the included studies measured pain on different scales, and pain evaluation was subjective, especially for children.…”
Section: Discussionmentioning
confidence: 98%
“…But in our study, we used two different concentrations of levobupivacaine combined with same dose of ketamine (0.5 mg/kg) which enable us to determine the effect of ketamine when combined with caudal levobupivacaine. Our opinion is supported by Dobereiner et al, as they showed in their studies that if the local anesthetic agents are used in high doses, there will be no difference in postoperative analgesic efficacy [29].…”
Section: Discussionmentioning
confidence: 60%